Operations research and enterprise systems : 7th International Conference, ICORES 2018, Funchal, Madeira, Portugal, January 24-26, 2018, Revised selected papers /: 7th International Conference, ICORES 2018, Funchal, Madeira, Portugal, January 24-26, 2018, Revised selected papers. (2019) - Unknown
No abstract available